English as a foreign language instruction in Ecuador: Implementation of the Content and Language Integrated-Learning during 2019-2021 - Pamela Barre; Jhonny Villafuerte-Holguin (English Language Teaching Educational Journal, 2021)
Ecuadorian educational policy for English as Foreign Language instruction in Ecuador mandated in 2016 to introduce Content and Language Integrated-Learning (CLIL) methodology to improve the teaching and learning process. This research aims to analyze the implementation of CLIL methodology in zone 4 of Ecuador during 2019-2021. This work subscribed to the transformative paradigm and administrated quantitative and qualitative methods of educational research. The participants were 70 English as a Foreign Language teachers from nine public and private educational institutions located in Manabi Province of Ecuador. The instrument used was the Instructor Perceptions of Differentiated Instruction of Turner, Solis, and Kincade (2017) in an observation format. The information collection techniques used were in-depth interview and focus group discussion. The results allowed the research team to determine the impact of the pandemic on the CLIL implementation in zone 4 of Ecuador. The results show differences in the implementation of the methodology between public and private schools which are linked to internet and technology devices access, teachers' knowledge regarding CLIL methodology, and institutional policies. In regards COVID19 pandemic, it is concluded that it has pacted the implementation of CLIL methodology in both public and private secondary schools that participated in the study.